Электоральные революции как фактор политической модернизации : опыт Чехии и Словакии - БАШМАКОВ, Димитрий С. (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2007)
This paper discusses the transformation process of political systems in the Czech Republic and in Slovakia following the velvet revolution; the significance of civic society in the selfformation of political orientations and institutions via electoral revolutions is also considered.
Electoral revolutions as a factor of political modernization. The Czech and Slovak experience